A Biblioteca como Organização Aprendente: o desenvolvimento de competências em informação no Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Almeida, Jobson Louis Santos de (2015)
The library as a learning organization the educational role of developing skills in information on their servers, so that they are equipped with knowledge, skills and autonomy to search, access and use information in various learning situations. This consists of a challenge in the libraries belonging to the Federal Institutes of Education, because this display noticeably different complexity and purpose of the types of conventional libraries, such as school and university. Training education of users, much has been done to make the library a place of learning in recent decades, but there is still scientific studies apregoem that educational practices already adopted by other libraries are effective in this new library profile. Lack theoretical statements in the scientific literature to present this new librarian profile, active in the aforementioned organizational context, how important the educational project management combined with a learning organizational philosophy to the development of skills in information. The study is therefore proposed to investigate the relationship between the educational project development skills in information and the transformation of conventional library into a learning organization in the interdisciplinary theoretical and conceptual perspective of Social Sciences and Education. Methodologically the research is outlined as action research, qualitative and descriptive exploratory level. We used the techniques of literature search, document research, participant observation and organization categories to achieve the objectives outlined. The survey results make it possible to understand that the library of the Federal Institutes of Education, can be classified as a new type library for its intended purpose and should be called multilevel library, to cater for users of varying levels of education and training, a fact that differs from the established type library. To this end, it established a conceptual network of organization and articulation of categories, providing opportunities for the production of an educational project built from the descriptive study of a library of the campus of the Federal Institute of Paraíba Education, given the purpose of Professional Master's help the elucidation and improving organizational reality, from a scientific research. After all, an educational project template with the ability to be applied in various libraries of the Federal Professional Education Network, science and technology is unprecedented and promising. It concludes that the establishment of the educational project helps in the transformation of conventional library into a learning process library and the future implementation of the educational project, its monitoring and evaluation will reveal the possibilities and limitations of the process in relation to information regime.